Implementation of Drug Information Media on Drug Drinking Compliance of Outpatient Patients in Petaling Primary Healthcare - Syamsul Rizal Sinulingga (Jurnal Pengemas Kesehatan, 2024)
One of the regions in Indonesia is the Bangka Belitung Islands Province (Babel). In general, the administrative area of ​​Babel province consists of two main islands, namely Bangka and Belitung islands. Apart from that, there are also small islands around it, both inhabited and uninhabited. Among them is the island of Petaling Banjar Village, Kec. Mendo Barat Kab. Bangka Province of the Bangka Belitung Islands. The material used in carrying out this activity is implemented directly to outpatients, in collaboration with the Petaling Community Health Center. The pretest results showed that the majority (76.7%) of respondents had low compliance. In the posttest, the results showed that there was an increase in the number of respondents in the medium category from 23.5% to 33.3%. The conclusion is that there is a change in compliance in the moderate category from 23.5% to 33.3%.